The date and authorship of the Vita Ædwardi regis. (18th November 2016) - Licence, Tom
Abstract: Scholarly understanding of the reign of Edward the Confessor is hampered by doubt surrounding the date, authorship and purpose of the Vita Ædwardi regis, its chief biographical source. This article rejects readings that see it as a work written after the Conquest, arguing instead that it was begun in 1065–6 and tried to foresee what would happen in that time of upheaval by optimistic inspection of precedents from Godwine family history, tempered by anxious reflections on pagan Antiquity. Through the prophetic insights of history it finely balanced Edith's hopes and fears. The second part of the article considers evidence that helps us to identify an author.